PERAN KEPOLISIAN DALAM PENERAPAN HUKUM PIDANA TERHADAP ANAK DIBAWAH UMUR SEBAGAI PELAKU PENGGUNA NARKOBA (Studi Kasus Polda Sumatera Utara) - Yeltriana, Ricky Hermawan Ginting, (NERACA KEADILAN, 2025)
Drugs are currently one type of social pathology that is very worrying because in addition to being contrary to morals and laws, including health, physical and spiritual development of young people. But more worrying for many people and many countries is that drug abuse has grown into one of the elements and symbols of a new lifestyle. Drug abuse is currently not only dominated by adults, but also found drug users who are stilli n junior high school and high school. This legal problem concerns the role of law enforcement officers, especially the police whose existence is very important in society. The purpose of this study is to determine the role of the police in handling cases of minors asdrugperpetratorsandtofindoutwhatobstaclesarefacedbythe police in handling drug crime cases committed by children in the North Sumatra area. This type of research is qualitative and usesnormativeand empirical designs. Theresults of this study are that the role of the police in handling drug crime cases is started from several efforts, namely "Preemptive" efforts or actions or strategies carried out first to prevent by providing counseling, installing banners about the dangers of drugs, and working together with the community and Bhabinkamtibmas. Then, preventive efforts are control measures taken to prevent or reduce the possibility of criminal acts, for example, routine patrols, and the last is repressive efforts, namely efforts to take action after the crime has occurred. In handling drug crime casescommitted by police children, they also face several obstaclesin termsof the time of the investigation process, lack of public awareness and lack of family role.